Bio-derived polymers for coating applications: comparing poly(limonene carbonate) and poly(cyclohexadiene carbonate) - Stößer, T; Li, C; Unruangsri, J; Saini, P; Sablong, R; Meier, M; Williams, C; Koning, C (Royal Society of Chemistry, 2017)
Two fully bio-based polycarbonates, poly(cyclohexadiene carbonate) (PCHDC) and poly(limonene carbonate) (PLC), were synthesised from carbon dioxide and cyclohexadiene oxide and limonene oxide. The low molecular weight polycarbonates were cross-linked by a photoinitiated reaction with trimethylolpropane tris(3-mercaptopropionate), via thiol-ene reactions. The cross-linking reactions were monitored using Raman spectroscopy and the reaction temperatures and times were optimised. Kinetic analyses of the cross-linking process suggested diffusion-controlled reactions for both polymers, despite the differences in the nature of alkene moieties (terminal vs. internal alkene). The resulting materials were evaluated for coating applications, they showed showed promising solvent resistance and hardness and may be used in the future to prepare scratch-resistant coatings.